Effects of the fermentation quality and microbial community of waxy maize mixed with fodder soybean silage - Yang, Mei; Wang, Fengdan; Xu, Wen; Li, Xiaoming; Yin, Hang; Tuluhong, Muzhapaer; Qiu, Rui; Li, Bing; Cui, Guowen (Frontiers in Microbiology, 2024)
Waxy maize (Zea mays L. sinensis Kulesh) is highly regarded for its high nutritional content and unique taste. Although the stalks and leaves contain high carbohydrate levels after ears harvesting, inadequate crude protein (CP) limits the utilization and promotion of waxy maize silage in animal husbandry. In this study, waxy maize and fodder soybeans were mixed for sowing in different proportions (1:0 (CK), 1:1 (A1), 1:2 (A2), 1:3 (A3), and 1:4 (A4)) to investigate the effects of different mixing ratios on the growth of the waxy maize, the chemical indices, fermentation quality, and the microbial community of the mixed silage after ears harvesting. The mixed planting of waxy maize and fodder soybeans in different proportions had no effect on the yield and quality of the waxy maize ears, and increased the aboveground biomass after ears harvesting. After ears harvesting, the NDF and ADF contents significantly decreased, and the CP content and RFV gradually increased in the mixed silage. The pH of the treatments was lower than 4.2 except for A4, and the lowest AN concentration was observed in A3. With increasing proportions of fodder soybeans, the abundance of beneficial bacteria increased and that of harmful bacteria decreased; Firmicutes and Lactobacillus were the dominant phylum and genus, respectively, and both increased gradually. RDA revealed that the fermentation indices affecting the microbial community composition in the silage were inconsistent among the different mixed-sowing combinations. The Mantel test showed that the composition of the microbial communities in the treatments were significantly correlated with the ADF, WSC, and PA contents. Comprehensive analysis revealed that the optimal mixed-sowing ratio of waxy maize to fodder soybeans was 1:3, and waxy maize and fodder soybeans silage can increase the utilization of aboveground biomass and improve the fermentation quality and feeding quality of silage by changing the microbial community. These findings lay a certain theoretical foundation for improving the utilization of waxy maize.